Utilization of carob seed germ meal in tilapia diet - Fadel, Abdalbast H. I. (2018)
The cost of commercial feeds for farmed fish continues to soar leading to the need to explore new alternative ingredients that can economically meet the metabolic needs of cultured tilapia. In this study, a series of experiments was conducted to investigate the nutritional value and the optimum inclusion level of carob seed germ meal (CSGM) as a substitute for soybean meal (SBM) in red tilapia feed. In Experiment I, five isonitrogenous diets with increasing inclusion levels of untreated CSGM from 0-40% were tested. An inclusion of up to 30% untreated CSGM did not affect the growth and survival of red tilapia. However, the body biochemical composition and histopathological parameters indicated that fish health was compromised. Therefore, a maximum dietary inclusion of 20% untreated CSGM was recommended as a replacement of SBM for red tilapia. In Experiment II, the efficiency of roasting, soaking, and autoclaving in reducing antinutritional factors (ANFs) in CSGM was evaluated. ANFs and functional properties of CSGM significantly decreased after all pre-treatment processes particularly the 30- min autoclaving. However, soaking appeared to be the most optimum and straight forward solution for decreasing ANFs while simultaneously maintaining nutrient value and functionality of CSGM. Six experimental diets were formulated in Experiment III to contain 30 and 40% soaked CSGM, and 30 and 40% autoclaved CSGM with 0% and 40% untreated CSGM as negative and positive controls, respectively. Soaked or autoclaved CSGM at the 30% dietary inclusion level led to enhanced performance of CSGM in red tilapia compared untreated CSGM although not to the level of performance obtained with the CSGM-free diet. In Experiment IV, apparent digestibility coefficients (ADC) of untreated, soaked and autoclaved CSGM were determined. ADCs of nutrients and energy in untreated CSGM were significantly lower than those of soaked and autoclaved CSGM. Soaked CSGM had substantially better ADCs of nutrients and energy than autoclaved CSGM. Experiment V was aimed to increase the digestibility of CGSM by in vitro and in vivo application of β-mannanase and α-galactosidase mixture. In vitro results demonstrated that smaller particle size of CSGM yielded a higher mannose at 0.1% of enzyme hydrolysis with lower fibre content than other treatments. Whereas in vivo results showed that the growth performance and feed utilization of fish fed enzyme pretreated CGSM were not significantly different from those of fish fed CGSM-free diet. Fish fed a diet without enzyme pre-treated CSGM had significantly higher intestinal short chain fatty acids (SCFA) whereas body protein and lipid, muscle cholesterol, and plasma cholesterol and glucose were significantly lower than those in fish fed other pre-pretreated CSGM. In conclusion, untreated CSGM could be used as a partial substitute of soybean meal in the red tilapia diet up to 20% dietary inclusion. Pre-treating CSGM by soaking for 24h and followed by a carbohydrase treatment significantly improved its nutritional quality and increased its optimal inclusion level to 30% of diet.